ON THE PROBLEM OF ONTOLOGY AND TERMINOLOGY OF STATUSORIENTED TYPES OF DISCOURSE IN MODERN LINGUISTIC DISCOUROLOGY - I. V. Chekulai; O. N. Prokhorova (Дискурс профессиональной коммуникации, 2019)
The article raises the problems of the status-oriented discourse typology. The essence of them lies in the fact that there exist several terminological nominations of such general type of the discourse, namely “institutional discourse”, “business discourse”, “expert discourse”, “specialized discourse”, “professional discourse”. These terminological nominations often overlap giving the effect of vagueness of a certain term. The genre versatility of the texts pertaining to some discourse cluster of a specialized (i.e. involving certain special knowledge at least from the part of one of the discourse participants) character is such a case. More than that, we often meet the same authors using different terms from the list above. Still, the authors of the article consider these terms to denote different essences differentiating not only from the nominative point of view, but ontologically as well. First, they are sure to denote hierarchically different levels of the status-oriented discourse. Second, they are sure to present peculiar to a certain types of a discourse categorical status of the communicants. Third, the coordination of oral and written discourse genres is bound to be peculiar to a certain kind of the discourse. All these considerations predetermine the common efforts of linguists to conduct systemic research of the problem.